Analisis Ekstrak Etanol Tangkai Daun Buasbuas (Premna pubescens) Menggunakan Gas Chromatography Mass Spectrophotometer (GCMS) - Diky Setya Diningrat; Martina Restuati; Kusdianti Kusdianti; Ayu Nirmala Sari; Erly Marwani (Elkawnie, 2018)
Buasbuas (Premna pubescens) is a plant that is traditionally known to have medicinal properties. This study aims to determine the content of bioactive compounds contained in the petiole by Gas Chromatography Mass Spectrophotometer (GCMS) method. Preparation of ethanol extract of petiole using maceration method with 96% ethanol solvent. The study used gas chromatographic tools and mass spectra which were evaluated using MASSLAB program. The data obtained from the GCMS machine is then analyzed using the NCBI database pubchem software (https://pubchem.ncbi.nlm.nih.gov/). The results of this study indicate that the content of bioactive compounds on the petioles of buasbuas more than 50 libraries contains about 150 species of compounds with a range of RT and% area respectively 4.684 to 28.155 and 0.16 to 15.56%. The content of bioactive compounds shown this data indicates that very large potential of buasbuas plants to be explored and exploitation as a nutritious plant. The results of this study can be used as the foundation in the development program of the potential utilization of bioassemblance of buasbuas plants. In further research it is necessary to analyze the other parts of the plant and make comparisons to complete the available databases.